Engineered neural tissue with aligned, differentiated adipose-derived stem cells promotes peripheral nerve regeneration across a critical sized defect in rat sciatic nerve. (January 2015) - Georgiou, Melanie; Golding, Jon P.; Loughlin, Alison J.; Kingham, Paul J.; Phillips, James B.
Abstract: Adipose-derived stem cells were isolated from rats and differentiated to a Schwann cell-like phenotype in vitro . The differentiated cells (dADSCs) underwent self-alignment in a tethered type-1 collagen gel, followed by stabilisation to generate engineered neural tissue (EngNT-dADSC). The pro-regenerative phenotype of dADSCs was enhanced by this process, and the columns of aligned dADSCs in the aligned collagen matrix supported and guided neurite extension in vitro . EngNT-dADSC sheets were rolled to form peripheral nerve repair constructs that were implanted within NeuraWrap conduits to bridge a 15 mm gap in rat sciatic nerve. After 8 weeks regeneration was assessed using immunofluorescence imaging and transmission electron microscopy and compared to empty conduit and nerve graft controls. The proportion of axons detected in the distal stump was 3.5 fold greater in constructs containing EngNT-dADSC than empty tube controls. Our novel combination of technologies that can organise autologous therapeutic cells within an artificial tissue construct provides a promising new cellular biomaterial for peripheral nerve repair.